Safety Helmet Fit Assessment Using 3D Scanning and Helmet Fit Index (HFI) - Azlan, Syahrizan; Nur Fitrah Najiha Muhamad Dzahir; Mustafa El Bakri, Helmy; Mahmood, Salwa (International Journal of Integrated Engineering, 2024)
Safety helmets, essential in industries like construction, mining, and sports activities, are designed to protect the head from impact and penetration injuries. However, the effectiveness of these helmets is often compromised by issues of poor fit, discomfort, and non-compliance with safety protocols. The primary objective of this research is to evaluate the fit of safety helmets using the Helmet Fit Index (HFI) and 3D scanning. A sample group of 100 male participants aged between 20 and 50 is involved in this study. The methodology includes 3D scanning of participants’ heads with and without safety helmets, followed by post-processing. The HFI for safety helmets is typically expressed as a percentage which this index assigns a score ranging from 0 (indicating a very poor fit) to 100 (representing an ideal fit), indicating the proportion of users for whom the helmet adequately fits. The HFI results indicate a poor fit of safety helmet among the selected participants. The average HFI score of 18.62 observed across 100 participants, with scores varying between 7.94 and 47.79. The significant gap at the top for vertical clearance led to high measurements of Gap Uniformity (GU) and the Standoff Distance (SOD), reflecting inconsistencies in the fit. These high values contributed to a lower HFI score, indicating that the helmets were less secure and uncomfortable. Consequently, the helmets’ overall performance and safety effectiveness were compromised, underscoring the need for proper internal cushioning and minimal gaps to ensure optimal protection and fit.